Embedding Religious Values through the “Dodosidodo” Lullaby Tradition: A Culturally Rooted Approach to Early Childhood Education in Aceh Tamiang - Amalia, Rizka; Sirait, Sangkot (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2025)
This study investigates the transmission of religious values through the Ngayon Anak “Dodosidodo” tradition as practiced in early childhood parenting among the Tamiang ethnic community in Aceh Tamiang, Indonesia. The tradition, which involves mothers singing poetic lullabies while gently swinging their children, serves as a medium for embedding Islamic teachings and moral values such as monotheism, obedience, honesty, patience, and affection. Utilizing a qualitative ethnographic approach with a multi-site case study design, this research employed observation, in-depth interviews, and document analysis to explore the symbolic structure, functions, and educational significance of Dodosidodo. The tradition manifests in three symbolic forms: Berunjo (sitting posture with extended legs), Ipere’ (child in a swing), and Bele (gentle caress), each of which reinforces familial bonds and facilitates the internalization of ethical values during early developmental stages. The findings indicate that Dodosidodo not only supports emotional security and spiritual awareness in children but also acts as a form of informal religious instruction deeply rooted in cultural identity. However, the continuity of this oral tradition is threatened by modern childcare practices, digital media, and the declining use of local languages. This study highlights the urgency of preserving such traditions as culturally responsive pedagogical models that contribute to holistic early childhood education. The integration of indigenous practices like Dodosidodo into contemporary educational frameworks offers valuable insights for strengthening character education grounded in local wisdom and Islamic ethics.